“Not Just What We Dismantle but also What We Hope to Build”: Alicia Garza on Black Lives Matter and Digital Activism - Mulcahy, Clare (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
What follows is an interview with Alicia Garza about Black Lives Matter and the relationship between traditional and digital activism.